Effectiveness of Relaxation Breathing Exercise on fatigue in gynecological cancer patients undergoing chemotherapy - Mulhaeriah; Yati Afiyanti; Engkus Kusdinar Achmad; Moh Syafar Sangkala (Elsevier, 2018)
Purpose: This study aimed to determine the effectiveness of Relaxation Breathing Exercise (RBE) on fatigue in patients with gynaecological cancer undergoing chemotherapy. Methods: We used a quasi-experiment with pre- and post-test design. Forty-two patients were consecutively sampled, 21 of whom were assigned to the group receiving RBE four times a day and 21 to the group receiving RBE twice a day. Fatigue scores were measured every day for 7 days for both groups using the Piper Fatigue Scale. Data obtained were analysed using repeated-ANOVA and independent t-test with a significant level of α < 0.01. Results: We found a significant decrease (P < 0.01) in the mean fatigue scores of both groups (four times RBE in a day group = 3.29 ± 0.59 and twice RBE in a day group = 4.19 ± 0.61) after the completion of the intervention. However, the four times RBE a day group showed larger decrease on fatigue scores than the twice RBE a day group did (Mean Difference = 0.91; 99% CI = 0.41 to 1.41; P = 0.001). Conclusion: Conducting RBE four times a day effectively alleviated fatigue better than RBE twice a day on gynaecological cancer patients undergoing chemotherapy. Keywords: Relaxation breathing exercise, Gynaecologic cancer, Chemotherapy, Fatigue